Study on Limitations of Economic Copyright in the Age of Generative AI under South Korea’s Copyright Act - JaeHoon Lee (International Journal of Advanced Culture Technology(IJACT), 2025)
With the rapid advancement of generative AI technologies, issues concerning copyright and the fair use of copyrighted works have grown increasingly complex. Despite the heightened attention to these challenges, clear legal frameworks to effectively address them remain lacking. In response to this gap, this paper is designed to serve as a starting point for research on balancing copyright law and the fair use of generative AI. This study examines the limitations of economic rights under South Korea’s Copyright Act and explores ways to align AIgenerated outputs with the existing legal system. In particular, the relevance between the limitations on economic rights and generative AI is quantified using a Ricardian-type scale. Additionally, it highlights the importance of addressing access to copyrighted works during the training of generative AI, particularly in data mining, where reproduction and transmission may occur without authorization from rightsholders. By investigating these issues, the study seeks to contribute to developing a more coherent and adaptable legal framework suited to the era of artificial intelligence.